Natural Products as a Source for New Anti-Inflammatory and Analgesic Compounds through the Inhibition of Purinergic P2X Receptors - Rômulo José Soares-Bezerra; Andrea Surrage Calheiros; Natiele Carla da Silva Ferreira; Valber da Silva Frutuoso; Luiz Anastacio Alves (MDPI AG, 2013)
Natural products have reemerged in traditional medicine as a potential source of new molecules or phytomedicines to help with health disorders. It has been established that members of the P2X subfamily, ATP-gated ion channels, are crucial to the inflammatory process and pain signalization. As such, several preclinical studies have demonstrated that P2X2R, P2X3R, P2X4R and P2X7R are promising pharmacological targets to control inflammatory and pain disorders. Several studies have indicated that natural products could be a good source of the new specific molecules needed for the treatment of diseases linked to inflammation and pain disorders through the regulation of these receptors. Herein, we discuss and give an overview of the applicability of natural products as a source to obtain P2X receptors (P2XR) selective antagonists for use in clinical treatment, which require further investigation.